A study of the composition of the products of laser-induced breakdown of hexogen, octogen, pentrite and trinitrotoluene using selected ion flow tube mass spectrometry and UV-Vis spectrometry - Sovová, Kristýna; Dryahina, Kseniya; Spanel, Patrik; Kyncl, Martin; Civis, Svatopluk (The Analyst, 2010)
Four types of explosives were studied using a combination of Laser Induced Breakdown Spectroscopy (LIBS) and Selected Ion Flow Tube Mass Spectrometry (SIFT-MS). The LIBS technique uses short laser pulses (ArF excimer laser) as the energy source to convert small amounts samples into plasma and to produce the emission from their molecular fragments or atoms. SIFT-MS is a novel method for absolute quantification based on chemical ionization using three precursor ions, with the capability to determine concentrations of trace gases and vapours of volatile organic compounds in real time. This is the first time that SIFT-MS has been used to study the release of NO, NO(2), HCN, HNO(3), HONO, HCHO and C(2)H(2) after a laser-induced breakdown of pure explosive compounds HMX (1,3,5,7-tetranitro-1,3,5,7-tetraazacyclo-octane), RDX (1,3,5-trinitro-2-oxo-1,3,5-triazacyclo-hexane), PETN (pentaerithrityl-tetranitrate) and TNT (2,4,6-trinitrotoluene) in solid form. The radiation emitted after excitation was analysed using a time resolving UV-Vis spectrometer with a ICCD detector. Electronic bands of the CN radical (388 nm), the Swan system of the C(2) radical (512 nm), the NH radical (336 nm), the OH radical (308.4 nm) and atomic lines of oxygen, nitrogen and hydrogen were identified. Vibrational and excitation temperatures were determined from the intensity distributions and a scheme of chemical reactions responsible for the formation of the observed species was proposed.